Functionalities as a Service - An Approach to Conciliate Interoperability and Data Reduction in E-Health - Costa, João Pedro de S. J. da; Dantas, Mário A. R.; David, José Maria N.; Silva, Fernando de Almeida (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2023.235668, 2023)
Interoperability and data reduction have been proven beneficial to health and medical applications that deal with large datasets. Still, the conflicts between these qualities turned out to be a problem for their conciliation. This paper presents an edge-fog-cloud architecture that offers functionalities as a service. These functionalities can guarantee certain qualities depending on the necessities of the client, such as, in our case, interoperability and data reduction. With the use of context simulators, we found that it was possible to significantly increase the output of data delivered to the servers, and decrease the size of the data that transitions in the network and is stored in the servers’ databases, without interfering with the syntactic interoperability.